#TITLE_ALTERNATIVE# - BHASWARA (NIM : 13606044); Tim Pembimbing : Dr. Ir. M.Giri Suada.; Dr. Ir. Leonardo Gunawan, AWANG
The offshore oil and gas industry is operating in increasingly demanding environmental conditions of deeper water and harsh weather. The need among engineers, drilling managers and floating production operators for detailed and accurate riser analysis and verification studies is greater than ever. The track record of Top tension Riser has been well established for deepwater applications in Indonesia since 2003, located in West Seno block- Makassar strait Indonesia.. In early 2000, the hybrid riser concept has been established as a viable solution for deepwater developments, but only a handful concept exist. The length of riser structure could be more than thousand meters base on the sea depth. Depend on the riser operation, the velocity of sea current around the long riser vary with the depth of the sea, and create velocity gradient along the riser ( sheared flow ). The flow around the riser is dominated by vortex flow because the riser profile is bluff body profile. The vortex flow around the riser profile generates vortex shedding frequency. If the vortex shedding frequency is near or equal to a natural frequency of the riser, the vortex shedding will induce the riser to vibrate and cause fatigue failure. That known as vortex induced vibration phenomenon ( VIV ) in riser. This final project presents analysis and comparison results of vortex induced vibration lead to fatigue damage of top tension riser and hybrid riser. The work consists of modeling of structural dynamic, and response analysis of the riser due to sheared flow. Structural dynamic modeling was performed using finite element method implemented in PATRAN NASTRAN. The vortex induced vibration analysis and fatigue damage implemented in SHEAR 7 module for the dynamic riser response due to sheared flow. Structural dynamic modeling was performed using finite element method implemented in PATRAN NASTRAN. The vortex induced vibration analysis and fatigue damage implemented in SHEAR 7 module for the dynamic riser response due to sheared flow.